The problem of early human in the territory of the Khovd aimag : : A review of Stone Age research and main sites - Yadmaa, Tserendagva (Studia Archaeologica, 2024)
The study of Stone Age Khovd Aimag, began in the 1950s. Joint Mongolian-Soviet Union archaeological team for studying Stone Age and joint Mongolian-Soviet Union historical and cultural expedition played a major role in the study of Stone Age in the territory Khovd Aimag. At present, 102 sites related to the Paleolithic, Mesolithic, Neolithic periods have been discovered and studied. These sites and stone tools from them show that starting from the Lower Paleolithic, ancient people began to settle in the intermountain plains, where are many animals for hunting, and in the basin of large rivers of the Mongolian Altay. Ховд аймгийн нутагт эртний хүн суурьшсан асуудал: чулуун зэвсгийн судалгааны тойм, дурсгалууд Товчлол. Ховд аймгийн нутаг дэвсгэр дэх чулуун зэвсгийн үеийн дурсгалыг судлах ажил 1950-аад оноос эхэлжээ. Тус аймгийн чулуун зэвсгийн судалгаанд Монгол, Зөвлөлтийн хамтарсан чулуун зэвсгийн судалгааны анги, МЗТСХЭ голлох үүрэг гүйцэтгэсэн юм. Одоогийн байдлаар тус аймгийн нутгаас палеолит, мезолит, неолитын үед холбогдох 102 дурсгалт газар илэрч, судалгааны эргэлтэд ороод байна. Дээрх дурсгалт газар, олдвор хэрэглэгдэхүүнээс харахад доод палеолитын үеэс эхлэн Монгол Алтайн нурууны томоохон гол мөрний сав, уул хоорондын ан амьтан элбэг үржил шимт хөндий бараадан эртний хүмүүс амьдарч байсан нь батлагддаг. Түлхүүр үг. Ховд аймаг, чулуун зэвсэг, доод палеолит, дунд палеолит, дээд палеолит, неолит, чулуун зэвсгийн үйлдвэрлэл.